Convergences between Postmodern Thesis on 'The Death of the Subject' and the Thought of Luce Irigaray - Ara Anel, Alba (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
The Postmodern thought stands as one of the philosophical movements that have achieved a greater repercussion in present times. The Difference Feminism, a current arising in the 60s and 70s, converges in many of its premises with those generally attributed to Postmodernity. In this article both trends are put in dialogue, starting from the revision of some of feminist theorist Luce Irigaray’s approaches that refer to the later theorized ‘Death of the Subject’ - one of the axes of Postmodern thought. This thesis translates into Irigaray as critic of the construction of the ‘Man’ as an universal and central subject in patriarchal order, which defines women as men’s opposite and subsequently renders them deprived of their own subjectivity. Irigaray challenges the existence of this universal subject through her call to discover women’s own subjectivity as a starting point from which an alternative symbolic order can be established. However, it is also possible to identify some contradictions between both theories.
Keywords: posmodernism; feminism; difference; subjectivity; phallocentrism; language